Clinically Relevant Pharmacogenomic Testing in Pediatric Practice. (August 2014) - Korbel, Lindsey; George, Mathew; Kitzmiller, Joseph
Clinicians and patients continue to convey interest in personalized medicine. The objective of personalized medicine is to improve healthcare by tailoring disease prevention, diagnosis, and treatment strategies for individuals based on their unique clinical history and genetic composition. This article offers an overview of pharmacogenomics, discusses caveats specific to pharmacogenomics in pediatric populations, provides evidence-based recommendations for pediatric clinicians, and offers insight regarding the future role of pharmacogenomics testing in pediatric medicine. Reviews of the current literature and thoughtful discussions are presented regarding the pharmacogenomics of antidepressants, codeine and oncologic, asthma, and immunomodulatory pharmacotherapies.